Intraoperative Ultrasonography in Endoscopic Approaches for Orbital Lesions: A Single-Center Case Series. Issue 1 (1st January 2023) - Zoli, Matteo; Sollini, Giacomo; Martinoni, Matteo; Rustici, Arianna; Guaraldi, Federica; Asioli, Sofia; Fabbri, Viscardo Paolo; Cirillo, Luigi; Pasquini, Ernesto; Mazzatenta, Diego
Abstract : BACKGROUND: Recently, endoscopic approaches for orbital lesions have been proposed. Their results seem promising; however, orbital surgery remains challenging with possible significant morbidity, mostly because of orbital structures manipulation. Ultrasonography is an innovative intraoperative imaging technique that can assist the surgeon in these approaches. OBJECTIVE: To assess the role of intraoperative ultrasound (IOUS) in endoscopic orbital surgery. METHODS: All consecutive patients with orbital tumors operated in our institution through an endoscopic approach with IOUS have been prospectively collected from 2019 to May 2021. RESULTS: Fifteen patients were included. Based on tumor location, evaluated on preoperative MRI, the endoscopic endonasal approach was preferred in 7 tumors in medial quadrants while the endoscopic transpalpebral in 8 lateral ones. During surgery, IOUS allowed us to identify the tumors and the most relevant anatomic structures in all cases. Time spent for IOUS preparation before the first scan was 8 ± 6 minutes on average, and each intraoperative scan took approximately 30 to 120 seconds. Gross tumor removal was achieved in 8 patients, subtotal in 3, while in 4 patients, surgery was limited to a biopsy. No surgical complications were observed. CONCLUSION: IOUS has allowed us to localize the lesion and to identify the straighter surgical corridor and assess the tumor resection, effectively helping the surgeon and potentially reducing operative complications. This tool provides a real-time image, not affected by the orbital structures shift, which can be dynamically assessed multiple times during surgery. However, it is hampered by the need of specific training and possible artifacts.